MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) IPA MELALUI MODEL TRANSFORMATIVE LEARNING PADA SISWA KELAS III SDN KENARI 07 KOTA JAKARTA PUSAT - Widya Khairunisa; TunjungSari Sekaringtyas; Yurniwati Yurniwati (STKIP Subang, 2026)
This study was conducted due to the low Higher Order Thinking Skills (HOTS) of third-grade elementary school students in science learning, particularly on the topic of changes in the states of matter. This study aimed to improve students’ HOTS through the implementation of the Transformative Learning model. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted in three cycles consisting of planning, action, observation, and reflection. The participants were 25 third-grade students of SDN Kenari 07, Central Jakarta. Data were collected through HOTS essay tests, observation sheets, documentation, and field notes, and analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of the Transformative Learning model improved students’ HOTS in every cycle. Learning mastery increased from 60% in Cycle I to 72% in Cycle II and reached 88% in Cycle III. The average HOTS score also increased from 76.00 in Cycle I to 76.50 in Cycle II and reached 85.40 in Cycle III. In addition, the HOTS indicators of analyzing (C4), evaluating (C5), and creating (C6) increased to 34.80%, 26.70%, and 24.60%, respectively, with the overall HOTS achievement reaching 86.10% in Cycle III. Therefore, the Transformative Learning model effectively improves elementary school students’ Higher Order Thinking Skills in science learning.